Pengaruh NPF, BOPO, Inflasi dan Nilai Tukar Terhadap Kinerja (ROA) pada Bank Umum Syariah Masa Pandemi Covid 19 - Milda Handayani; Muhammad Richo Rianto; Ari Sulistyowati; Supriyanto Supriyanto (ITB AAS INDONESIA Surakarta, 2022)
This study is a measurement of microeconomic variables using non performing financing (NPF) and operating costs (BOPO) and macroeconomic variables using inflation and exchange rates on performance using the profitability ratio (ROA) at Islamic commercial banks during the covid-19 period. This study is a quantitative design study with the object of research being Islamic commercial banks in Indonesia during the COVID-19 pandemic. Sampling in this study used purposive sampling with a total of 3 Islamic Commercial Banks. IBM Statistical SPSS version 23 program is the analytical method used in this study. The results of this study conclude that microeconomic variables that use NPF and BOPO affect the performance of Islamic Commercial Banks during the covid 19 pandemic. Meanwhile, macroeconomic variables with inflation and exchange rates have different results, where inflation has an effect on performance, but the exchange rate has no effect on the performance of Islamic Commercial Banks during the covid 19 pandemic. This study focuses on measurement using the financial ratio method. This research also makes a new contribution to the phenomenon of Islamic commercial banks during the covid 19 pandemic. This research can also be input and an overview of strategies that can be taken by related parties so that they can improve positive performance, especially in dealing with extraordinary conditions such as the COVID-19 pandemic.